Fun-tastic English Club guna Meningkatkan Kemampuan Berbicara Bahasa Inggris Siswa SMP di Kecamatan Kramatmulya - Wahidin; Agustiana, Vina; Adawiyah, Siti Zulpa; Praptiwi, Septiana Dwi; Yulithalia Sianturi, Yulithalia (Yayasan Kajian Riset dan Pengembangan RADISI, 2025)
Speaking skills in English are essential for accessing global knowledge. However, many students struggle with shyness, low self-confidence, and a lack of interactive and enjoyable practice opportunities, which hinder their speaking development. One effective method to improve speaking skills is through News Anchoring, as it helps students practice expressing ideas, pronunciation, intonation, fluency, and news comprehension. To further support this development, extracurricular activities such as an English Club should be established outside regular school hours. The English Club serves as a strategic platform to provide practice opportunities, boost motivation, and build students' confidence in using English. The result of this community service program indicates a positive response from students, with their speaking skills improving from an average score of 3 to 4.6, after participating in the News Anchoring activities in the English Club.